Exposition et exhortation : deux facettes du discours écologique - Gaëlle Ferré (Anglophonia)
“Argumentative discourse aims at influencing the opinions, attitudes or behaviour of an addressee or an audience by making a statement credible or acceptable” (Adam, 1992: 116). There are however different ways of reaching this goal as will be shown in a collection of varied internet videos. This paper proposes an analysis of two styles present in ecological discourse which can be expositive in nature but can also be closer to exhortation as environmentalists wish to urge people and governments to act on the issue of global warming. A difference of multimodal complexity and/or intensity is observed between the two styles.Expository discourse will be shown to be expressed in speech with the use of examples and explanations of processes and systems. Renaming and defining is very much present in this type of discourse. Prosodically close to pedagogical discourse, expository discourse is typically uttered with greater emphasis. Multimodally, this type of discourse relies on visual resources (slideshow, maps, etc.) and speakers’ gestures mostly include three types: discourse organisation gestures, pointing to visual resources, and representational gestures (McNeill, 2005) which illustrate the verbal content in speech and may even complement other types of visuals.For its part, exhortation will be shown to be expressed by hyperbolic speech (Druetta, 2015a; Ferré, 2014), metaphor and contrasts. Beat prosody is also more present in this type of discourse, accented syllables being closer to each other and more often pronounced with emphatic prosody: syllable lengthening, but also higher pitch, as well as potentially larger pitch movements and higher speech amplitude (Brenier et al., 2005; Herment-Dujardin & Hirst, 2003; Simon & Grobet, 2005). Prosodic beats are regularly accompanied by beat gestures (Biau & Soto-Faraco, 2013; Dimitrova et al., 2016; Ferré, 2019) while contrasting viewpoints can be expressed in hand gestures being performed in different parts of the speaker’s personal space (McNeill et al., 1993).